1998
DOI: 10.1044/jslhr.4102.300
|View full text |Cite
|
Sign up to set email alerts
|

Temporal-Order Discrimination for Selected Auditory and Visual Stimulus Dimensions

Abstract: Thresholds for the discrimination of temporal order were determined for selected auditory and visual stimulus dimensions in 10 normal-adult volunteers. Auditory stimuli consisted of binary pure tones varying in frequency or sound pressure level, and visual stimuli consisted of binary geometric forms varying in size, orientation, or color. We determined the effect of psychophysical method and the reliability of performance across stimulus dimensions. Using a single-track adaptive procedure, Experiment 1 showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 66 publications
1
30
0
Order By: Relevance
“…2). This general pattern of results agreed favorably with our previous study in normal adults [22]. The ANOVA showed significant main effects of group, F 1,6 = 11.11, p < 0.02, stimulus dimension, F 4,24 = 4.05, p < 0.002, and test session, F 3,18 = 6.48, p < 0.004, on TOT.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…2). This general pattern of results agreed favorably with our previous study in normal adults [22]. The ANOVA showed significant main effects of group, F 1,6 = 11.11, p < 0.02, stimulus dimension, F 4,24 = 4.05, p < 0.002, and test session, F 3,18 = 6.48, p < 0.004, on TOT.…”
Section: Resultssupporting
confidence: 81%
“…The apparatus, stimuli and procedures were identical to those used in a previous study [22]. A brief account is provided here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reports examining performance on auditory relative-timing tasks include data only from trained listeners, implying that experience leads to improvement [asynchrony (Hirsh and Sherrick, 1961;Summerfield, 1982;Parker, 1988;Zera and Green, 1993a,b;Tillmann and Bharucha, 2002) and order (Hirsh, 1959;Hirsh and Sherrick, 1961;Swisher and Hirsh, 1972;Wier and Green, 1975;Miller et al, 1976;Pisoni, 1980;Pastore et al, 1982Pastore et al, , 1988Pastore, 1983;Kelly and Watson, 1986)]. For order-discrimination tasks, such improvements have been either specifically mentioned without supporting data (Broadbent and Ladefoged, 1959;Divenyi and Hirsh, 1974;Pastore, 1983;Kewley-Port et al, 1988;Pastore and Farrington, 1996) or reported with supporting data, including changes in performance during the training period (Nickerson and Freeman, 1974;Warren, 1974;McFarland et al, 1998), com-parisons between the performance of trained and untrained listeners (Barsz, 1996), or improvement from pretraining to posttraining (Merzenich et al, 1996). In each of these cases of documented learning, listeners improved significantly on a trained ordering task, in which two or more consecutive sounds (pure or complex tones and/or noises) were arranged in different orders, and listeners identified specific instances of (Warren, 1974;Merzenich et al, 1996) or discriminated between (Nickerson and Freeman, 1974;Barsz, 1996;McFarland et al, 1998;Takahashi et al, 2004) these orders.…”
Section: Introductionmentioning
confidence: 99%
“…For order-discrimination tasks, such improvements have been either specifically mentioned without supporting data (Broadbent and Ladefoged, 1959;Divenyi and Hirsh, 1974;Pastore, 1983;Kewley-Port et al, 1988;Pastore and Farrington, 1996) or reported with supporting data, including changes in performance during the training period (Nickerson and Freeman, 1974;Warren, 1974;McFarland et al, 1998), com-parisons between the performance of trained and untrained listeners (Barsz, 1996), or improvement from pretraining to posttraining (Merzenich et al, 1996). In each of these cases of documented learning, listeners improved significantly on a trained ordering task, in which two or more consecutive sounds (pure or complex tones and/or noises) were arranged in different orders, and listeners identified specific instances of (Warren, 1974;Merzenich et al, 1996) or discriminated between (Nickerson and Freeman, 1974;Barsz, 1996;McFarland et al, 1998;Takahashi et al, 2004) these orders. However, there is no similar documentation of learning on auditory asynchrony detection, nor has generalization to untrained conditions been explored for either auditory relative-timing task.…”
Section: Introductionmentioning
confidence: 99%